Linking Corporate Social Responsibility and Organizational Performance in WH Industrial Holdings Company in China - Dong, Jianbo; Perez, Jennifer. M (International Journal of Global Economics and Management, 2024)
The main objective of this study is to analyze the relationship between corporate social responsibility and organizational performance of WH Industrial Holdings Company. The study identified the profile of the respondents and determined the level of organizational performance in terms of financial and non-financial measures as assessed by the employees and how the employees perceive the corporate social responsibility practices of the company relative to economic, legal, ethical and philanthropic/discretionary aspects. It also determined how other stakeholders describe the CSR practices of the company.